ANALISIS KUALITAS WEBSITE KESYAHBANDARAN UTAMA MAKASSAR MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Andi Nur Anggraeni; Riyand Dwi Alamsyah M; Saharuddin (Nusantara Hasana Journal, 2023)
Kesyahbandaran Utama Makassar is one of the main ports in Indonesia, located in Makassar City, South Sulawesi Province. The Kesyahbandaran Utama Makassar website improves accessibility, efficiency, and user experience in interacting with Kesyahbandaran Utama Makassar. It is important to systematically evaluate the quality of government websites to ensure they can provide a good user experience and increase civic participation. System Usability Scale (SUS) is a method used to measure the usability of a system, such as websites, applications, or digital products. Using the above question types, SUS provides an overview of the user's perception of the usability of the system being evaluated. Based on the respondent's assessment recapitulation results, the average result of reusability to the system was 72.83, which was included in the GOOD category with a grade scale of C. It was concluded that the system built met the satisfactory feasibility status and could provide convenience to all users, both special and ordinary users.